Pengira Pelanggan Bersama Sistem Pengunci Pintu - Azman, Amir Muazzam; Ridzuan, Muhamad Haziq; Azman, Muhammad Amzar Wijdan; Mohamed Nor, Mohd Faizal (Multidisciplinary Applied Research and Innovation, 2022)
The use of customer counters is very useful in every premise at the moment in line with the pandemic situation that is plaguing our country. This is because with this customer counting system, it can facilitate the affairs of the premise manager in ensuring that each customer practices physical imprisonment and SOPs that have been set by the government. This project aims to create a prototype that serves to calculate the movement of customers in and out of a premise to prevent the risk of Covid-19 outbreak and thus avoid emerging clusters. This project uses PIR sensors to detect infrared signals. In addition, the project requires a servo motor to close the door automatically. This customer counting system can be controlled using a smartphone connected to Wifi via the Blynk app. The system also uses a buzzer that will sound if inward or outward movement is detected. LCD is also used to display the number of customers in a premises. The project operates with a smart detector and lock system. There are two methods that will cause the door to close, namely by controlling using a smartphone or when a red light comes on that indicates the number of customers in a premises has reached the limit.